2012
DOI: 10.1016/j.immuni.2012.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid-Sensing Toll-like Receptors Are Essential for the Control of Endogenous Retrovirus Viremia and ERV-Induced Tumors

Abstract: The genome of vertebrates contains endogenous retroviruses (ERVs) that are largely nonfunctional relicts of ancestral germline infection by exogenous retroviruses. However, in some mouse strains ERVs are actively involved in disease. Here we report that nucleic acid-recognizing Toll-like receptors 3, 7, and 9 (TLR 3, TLR7, and TLR9) are essential for the control of ERVs. Loss of TLR7 function caused spontaneous retroviral viremia that coincided with the absence of ERV-specific antibodies. Importantly, addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
166
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(181 citation statements)
references
References 69 publications
7
166
0
1
Order By: Relevance
“…RNA-sensing TLRs and the ssDNA cytosine deaminase apolipoprotein B mRNA-editing, enzymecatalytic, polypeptide-like 3 are other antiviral systems that affect mouse retroviruses, and also control the replication of endogenous retroviruses (ERVs) (16,(35)(36)(37). Therefore, ZAP might also contribute to the antiviral response to ERVs and prevent the ERV-induced generation of tumors in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-sensing TLRs and the ssDNA cytosine deaminase apolipoprotein B mRNA-editing, enzymecatalytic, polypeptide-like 3 are other antiviral systems that affect mouse retroviruses, and also control the replication of endogenous retroviruses (ERVs) (16,(35)(36)(37). Therefore, ZAP might also contribute to the antiviral response to ERVs and prevent the ERV-induced generation of tumors in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A coordinated B-and T-cell response is a well-established, pivotal defense mechanism against retroviral replication and pathogenesis (24)(25)(26). Innate immunity is also essential to control MuLV, which includes mechanisms that sense the virus and activate adaptive immunity (27), but also mechanisms that inhibit entry or transport to the nucleus, or interfere with reverse transcription accuracy and efficacy (13,28). NSG mice lack cells of the adaptive immune system (B-, T-and NK-cells) and have several defects in classic innate functions, including an absent hemolytic complement system, reduced dendritic cell function, and defective macrophage activity (10).…”
Section: Discussionmentioning
confidence: 99%
“…7 Interestingly, it has been shown that mouse Tlr3, Tlr7 and Tlr9 are essential for control of endogenous retroviruses (ERV). 8 ERVs are derived from past exogenous retroviral infections and constitute approximately 10% and 8% of mouse and human genomes, respectively. In this regard, Tlr3, Tlr7 and Tlr9 deficient mice show no induction of innate immune genes and the type I interferon response and these gene deficiencies result in high expression of ERV RNA leading to viremia and tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Tlr3, Tlr7 and Tlr9 deficient mice show no induction of innate immune genes and the type I interferon response and these gene deficiencies result in high expression of ERV RNA leading to viremia and tumorigenesis. 8 Like exogenous viruses, activation of TLRs via a variety of endogenous viral nucleic acids represents the initial step for downstream induction of NF-kB and/or IRF signaling pathways and stimulation of the interferon type I response (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%